Identification of a novel di-C-glycosyl dihydrochalcone and the thermal stability of polyphenols in model ready-to-drink beverage solutions with Cyclopia subternata extract as functional ingredient. (30th July 2021) - Human, Chantelle; Danton, Ombeline; De Beer, Dalene; Maruyama, Takuma; Alexander, Lara; Malherbe, Christiaan; Hamburger, Matthias; Joubert, Elizabeth
Graphical abstract: Highlights: Dihydrochalcones were the most thermally unstable compounds of C. subternata. di- C -Glucosyl 3-hydroxyphloretin degraded faster than its 3-deoxy derivative. The xanthones were less stable than flavones, a flavanone and a benzophenone. Degradation rate constants of compounds were calculated from second order kinetics. Citric acid decreased degration rates for the xanthones and dihydrochalcones. Abstract: Heat processing of ready-to-drink beverages is required to ensure a microbiologically safe product, however, this can result in the loss of bioactive compounds responsible for functionality. The objective of this study was to establish the thermal stability of a novel dihydrochalcone, 3′, 5′-di- β -d -glucopyranosyl-3-hydroxyphloretin (2 ), 3′, 5′-di- β -d -glucopyranosylphloretin (3 ) and other Cyclopia subternata phenolic compounds, in model solutions with or without citric acid and ascorbic acid. The solutions were heated at 93, 121 and 135 °C, relevant to pasteurisation, commercial sterilisation and ultra-high temperature (UHT) pasteurisation, respectively. For most compounds, the acids decreased the second order reaction rate constants, up to 27 times. Compound 2 (46.29 ± 0.53 (g/100 g) −1 h −1 ), and to a lesser extent compound 3 (5.94 ± 0.01 (g/100 g) −1 h −1 ) were the most thermo-unstable compounds when treated at 135 °C without added acids. Even though differential effects were observed for compounds at different temperatures and formulations, overall, the phenolic compounds were most stable under UHT pasteurisation conditions.